Age-related thymic activity in adults following chemotherapy-induced lymphopenia - Sfikakis, P.P.; Gourgoulis, G.M.; Moulopoulos, L.A.; Kouvatseas, G.; Theofilopoulos, A.N.; Dimopoulos, M.A. (European Journal of Clinical Investigation, 2005)
Background: The potential role of the adult thymus in T-cell homeostasis subsequent to lymphopenia remains the subject of debate. We examined whether thymic activity contributes to reconstitution of the peripheral T-cell pool, a critical process for patients recovering from antineoplastic therapy. Methods: In selected patients with various neoplastic diseases we assessed peripheral blood lymphocyte subsets by flow-cytometry, including thymus-derived, CD4+ T cells expressing the CD45RA molecule, and thymic size rebound by CT scan before, and 3, 6 and 12 months after completion of cytotoxic therapy. Results: Adult patients (n = 21, mean age of 30 years, range 18-49) had higher baseline numbers of B and lower numbers of NK cells than elderly patients (n = 15, mean age of 79 years, range 70-91), while total T-cell numbers did not differ. Despite the reduction of lymphocyte counts being comparable in the adult (mean of 45%) and elderly (mean of 49%) groups, occurring at, or near, completion of treatment, an enlargement of the previously atrophic thymus was evident in 63% of the adult, but in none of the elderly, subjects. In 22 patients who remained active disease-free during the following year, B cells and NK cells recovered to pretreatment levels as soon as at 3 months, whereas overall T-cell recovery occurred at 6 months post-treatment. Thymic rebound, observed in 11 of 22 patients who were of younger age, correlated significantly with a faster and more complete recovery of CD45RA+ CD4+ (mainly helper-naïve) T cells. Conclusion: The adult thymus appears capable of regeneration, at least up to middle age, contributing significantly to the reconstitution of the peripheral T-cell pool following chemotherapy-induced lymphopenia. In advanced age, however, although peripheral homeostatic pathways appear intact, regeneration of the naïve repertoire is incomplete. © 2005 Blackwell Publishing Ltd.
Keywords: Aging; Immune senescence; Lymphopenia; T-Cell; Thymus